Effects of dried distillers grains with solubles on sow carcass fat quality - Terry A Houser; A N Gipe; B L Goehring; S L Hillyard; A W Duttlinger; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2008)
A pilot experiment was conducted to determine the effects of feeding nonpregnant (open) sows a diet containing 50% dried distillers grains with solubles (DDGS) on growth and carcass fat quality. A total of 8 open sows were allotted to 1 of 2 diets by parity and BW. One diet was a standard corn-soybean meal-based gestation diet; the second diet was a corn-soybean meal-based diet that contained 50% DDGS. All sows were fed 5 lb/d of feed in a single feeding for 92 d. All sows were harvested on d 92 at the Kansas State University Meat Laboratory for determination of carcass fat quality. As expected, no differences in BW or backfat change were found (P>0.62) for the feeding period. Additionally, no differences (P>0.23) in lipid oxidation as measured by 2-thiobarbituric acid reactive substances (TBARS) assay were reported either initially or after 5 d of retail display for sows fed 50% DDGS compared with controls. Lipid oxidation increased (P<0.003) as measured by TBARS assay for both treatments from d 1 to 5 as expected. Jowl fatty acid analysis revealed an increase in linoleic acid (P<0.01), total polyunsaturated fatty acids (P<0.01), and the ratio of polyunsaturated fatty acids to saturated fatty acids (P<0.03). Also, there was a trend for increased jowl iodine value (P<0.08) for sows fed 50% DDGS compared with the controls. In summary, feeding 50% DDGS to open sows for 92 d did not significantly affect BW, backfat, and lipid oxidation compared with controls. However, feeding 50% DDGS increased the concentration of linoleic acid and total polyunsaturated fatty acids and tended to increase jowl iodine value compared with controls.; Swine Day, 2008, Kansas State University, Manhattan, KS, 2008
Keywords: Swine day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-074-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1001; Carcass fat quality; Dried distillers grains with solubles; Lipid oxidation; Sow